Enhancing the internet performance by restructur-ing IPV6 basic header - Batiha, khaldoun (International Journal of Engineering and Technology, 2018)
The infirmity of IPv4 in oblige the quickened development in requirements for unassigned IPv4 internet addresses blaze a trail for the emersion of new version of the internet protocol with quadruple address length to past all urgent need for web and applications in future using 128 bits address. Our paper highlights the major drawback in this new version of internet protocol which lies in its eighty presents overhead in the each packet fundamental header due to the origin and target addresses length which affect the internetworking performance. Then we nominate a solution after carrying out a study that aims to propose a new address length that enhances the general efficiency and utilization of the web and reduces the overhead by decreasing the address length. But at the same time is able to oblige the quickened development in requirements for assigned internet addresses in far future. This study produced a prediction table that predicts each IP address size between 32 bits and 64 bits in which year will all its available IP addresses for this size will be consumed.